A projectile point guide for the Upper Mississippi River Valley - Boszhardt, Robert F. (Bur Oak guide., 2003)
The most common relics of the 12,000-year occupancy of the Upper Mississippi River Valley may be the chipped stone projectile points that Native Americans fastened to the ends of their spears, darts, and arrow shafts. This useful guide provides a key to identifying the various styles of points found along the Upper Mississippi River in the Driftless region stretching roughly from Dubuque, Iowa, to Red Wing, Minnesota, but framed within a somewhat larger area extending from the Rock Island Rapids at the modern Moline-Rock Island area to the Falls of St. Anthony at Minneapolis-St. Paul.